Color Stability of Conventional and Bulk-Fill Resin Composites in Health-Oriented Beverages - Zeynep Hale Keles; Gorkem Sengez; Aliye Tugce Gurcan; Soner Sismanoglu (Materials, 2026)
Objective: To compare the color stability of a conventional nanofilled composite (Filtek Ultimate, FU) and a bulk-fill composite (Filtek Bulk Fill, FB) after immersion in health-oriented beverages. Materials and Methods: A total of 120 disc-shaped specimens (n = 10 per group) were prepared from the two composites and immersed for 12 days in distilled water (control), orange juice, green detox, red detox, pomegranate juice, or multivitamin water. Color coordinates (L*, a*, b*) were measured with a spectrophotometer at baseline and after immersion, and ΔL*, Δa*, Δb*, and ΔE were calculated using the CIELAB system. Data were analyzed using two-way ANOVA with Games-Howell and Welch’s t-tests (α = 0.05). Results: Material, immersion solution, and their interaction significantly affected all color parameters (p < 0.001). FB showed significantly higher ΔE than FU across all six solutions, including distilled water (p = 0.014). In FB, orange juice produced the highest color change (ΔE = 17.33 ± 1.61), followed by pomegranate juice (14.01 ± 0.33) and red detox (10.08 ± 0.72); in FU, ΔE ranged from 1.76 ± 0.76 (distilled water) to 5.16 ± 2.08 (orange juice). Orange juice caused a pronounced increase in lightness in FB (ΔL* = 16.12 ± 1.37), unlike the darkening produced by the other beverages. All beverage groups in both materials exceeded the acceptability threshold (ΔE = 2.7), whereas the distilled water controls of both materials remained below it. Conclusions: The bulk-fill composite was significantly more susceptible to discoloration than the nanofilled composite for all beverages. Health-oriented drinks, particularly orange, pomegranate, and red detox juices, produced clinically unacceptable color changes that should be considered in esthetic treatment and dietary counseling.